A Study of State Parameters for Road Construction of MSWI Bottom Ash - Nguyen, T. K. V.; Doan, T. T. H.; Cao, T. H.; Pham, H. S. (Engineering, Technology & Applied Science Research, 2021)
The current work tries to valorize the bottom ash from Municipal Solid Waste Incineration (MSWI). The bottom ash from waste incineration consists of atypical granular materials. They are industrial by-products resulting from the incineration of domestic waste and the way of the considered valorization is road gravel. In this paper, we present the state parameters of bottom ash taken from a recycling company in the North of France. These features can help us evaluate our bottom ash according to the technical guide of realization of embankments and subgrades.